NARRATIVES OF CRISIS: REPRESENTING CAPITALIST REALISM : PART I: GLOBAL PERSPECTIVES - Petsini, Penelope (Design/Arts/Culture, 2023)
Bringing together researchers, theorists and visual artists, this special issue aims to provide a platform for discussions and research, which consider various as- pects of the visual and its implication to both ideological formations and cultur- al forms related albeit not limited to the notion of crisis. The special issue is, in a way, a continuation of previous, relative- ly recent projects which the guest edi- tor has curated or organised, and most invited contributors have been involved in: The group exhibitions “Capitalist Re- alism: Future Perfect” and “Capitalist Realism: Past Continuous” (2018-19, held at MOMus-Thessaloniki Museum of Pho- tography and MOMus-Center of Experi- mental Arts, respectively)8, as well as the conference “Representing Capitalist Re- alism: Crisis, Politics and the Visual” (23- 24/11/2018, MOMus-Thessaloniki Museum of Photography & Rosa Luxemburg Foun- dation). Starting from this point, the issue aims to offer a comparative charting of the crisis discourse by adopting an inclu- sive definition of the term derived from new scholarship and the concept of “cap- italist realism” as introduced by MarkFisher.